2005
DOI: 10.1002/chir.20222
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism of heterochromophoric and partially regenerated purple membrane: Search for exciton coupling

Abstract: In order to determine the origin of the bisignate CD spectra of native purple membrane, heterochromophoric analogues containing bacteriorhodopsin regenerated with native all-trans-retinal and retinal analogues were investigated. The data collected for the purple membrane samples containing two different chromophores suggest the additive character of the CD spectra. This conclusion was supported by a series of spectra using 5,6-dihydroretinal and 3-dehydroretinal and by using 33% regenerated PM in buffer and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 71 publications
(46 reference statements)
2
25
0
Order By: Relevance
“…2d, 3d and 4d). In a previously reported AFM study, bO produced following the bleaching of WT‐bR were unable to form hexagonal lattices despite the retention of the trimeric unit (11). It is suggested that the lack of the correct BC loop structure in bO leads to the disorganized lattice formation (Figs.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2d, 3d and 4d). In a previously reported AFM study, bO produced following the bleaching of WT‐bR were unable to form hexagonal lattices despite the retention of the trimeric unit (11). It is suggested that the lack of the correct BC loop structure in bO leads to the disorganized lattice formation (Figs.…”
Section: Resultsmentioning
confidence: 98%
“…The results from atomic force microscopy (AFM) experiments have indicated that the trimeric form of bR is preserved in the PM, although the lattice disappeared following PM bleaching (8). In addition, the trimeric organization of partially and fully regenerated bR has been revealed by CD spectra (11), and the high yield of regenerated bR has been reported to be produced from thermally unfolded bO (12). These characteristics of retinal-reconstituted bR appear to be different to that of WT-bR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first possibility is based on excitonic interaction between sal and the retinal chromophore 21 . The second stems from the chiral conformation of the retinal in the presence of sal, while retinal-retinal excitonic coupling in a pigment pentamer form can be an additional cause for the CD spectrum 15,24,26,27 . Another possibility is based on a chiral conformation of sal in the presence of the retinal chromophore and nearby protein residues 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the CD spectra of native bR, and xR-sal complex were widely studied, the exact origin of the CD spectra is not completely clear 18,19,21,23,24,[27][28][29][30][31][32] . The CD spectra of native gR as well as in the presence of different types of carotenoids were studied previously, and it was proposed that the CD of the gR-carotenoid complex is due to induced chirality of the carotenoid 10,11 .…”
mentioning
confidence: 99%